CuxOy@COF: An efficient heterogeneous catalyst system for CO2 cycloadditions under ambient conditions. (December 2019) - Sengupta, Manideepa; Bag, Arijit; Ghosh, Swarbhanu; Mondal, Paramita; Bordoloi, Ankur; Islam, Sk. Manirul
Graphical abstract: Abstract: Synthesis of cyclic carbonates via CO2 cycloaddition reaction with epoxides is one of the promising strategies to valorize greenhouse gas CO2, thereby fixing it to the value-added chemicals. In this study, uniform copper oxide nanoparticles (Cu2 O, Cu4 O3 ) with variable oxidation states are stabilized by functionalized covalent organic frameworks (COF) and effectively utilized as a catalyst for the synthesis of cyclic carbonates under ambient temperature and atmospheric pressure. Characterization techniques e.g. powdered X-ray Diffraction (PXRD), high resolution transmission electron microscopy (HRTEM), Fourier transform infrared (FT-IR) and nitrogen physisorption (BET) coupled with DFT studies predict that the copper oxide nanoparticles are anchored on the mesochannels of covalent organic frameworks through a covalent-coordinate linkage. The catalyst exhibits significantly high turn over numbers (TON, order of 10 5 ) and more than 99% selectivity towards synthesis of cyclic carbonates with exceptional recyclability.